Phytomers, collet and founder cells: a “universal” plant embryonic body plan from a developmental, molecular, and evolutionary perspective - Venglat, Prakash; Vijayan, Perumal; Sharbel, Timothy F.; Rahman, Abidur; Tanino, Karen (Frontiers in Plant Science, 2025)
This article presents a novel perspective on plant embryogenesis, fundamentally differentiating it from the animal embryo model upon which plant models have long been based to discern the genetic and molecular mechanisms. We propose a plant embryonic body plan that aligns developmental and evolutionary insights across all five embryophyte groups (bryophytes, lycophytes, monilophytes, gymnosperms, and angiosperms). This conceptual model is grounded in a Reprogramming Potential (RP) involving an activation (RP1+) -suppression (RP1-) switch (RP1+/RP1-), which integrates embryonic development in a stepwise manner across diverse embryophytes. We further explore the evolutionary trajectory of this body plan, tracing the gradual assembly of the embryophyte genetic toolkit from bryophytes to angiosperms. Key developmental processes, such as the emergence of shoot and root meristems, vascular tissues, and seeds, are also examined within an evo-devo framework. Plant phenotypic plasticity, fundamental to their adaptation and survival, is manifested in two key hallmarks: (A) the iterative, modular growth of shoot and root units, and (B) their remarkable regenerative potential. While traditionally viewed as separate phenomena, we propose a novel, integrative model that connects these hallmarks within the context of plant embryogenesis. Our “proposed universal plant embryonic body plan” reconciles the genetic and molecular mechanisms of Arabidopsis thaliana embryogenesis with the contrasting developmental patterns observed in monocots. This unified model also integrates the concept of root founder cells and collet (shoot-root junction) into an embryonic framework facilitating the study of gene regulatory networks that underpin root evolution and its architecture.